Structural aspects of magnetic softening in Fe-based metallic glass during annealing. (15th January 2017) - Dai, J.; Wang, Y.G.; Yang, L.; Xia, G.T.; Zeng, Q.S.; Lou, H.B.
Abstract: Amorphous Fe81 Si9 B10 melt-spun ribbons were annealed at various temperatures to relieve the internal stress. Magnetic studies manifest the occurrence of magnetic softening. The structure evolution of samples was then investigated by synchrotron radiation X-ray diffraction. It was found that, from short-range order to medium-range order, a positive and negative sign for volumetric thermal strain alternates upon heating and the amplitude of strain decays. Moreover, extending to outer shells, thermal strain seems less temperature-dependent in terms of the rate of increment. Magnetic softening in Fe81 Si9 B10 metallic glasses upon annealing may result from the inhomogeneous thermal strains. Graphical abstract: (a) The volumetric thermal strains of amorphous ribbons annealed at various temperatures determined from G(r) peaks. (b) The volumetric thermal strains determined from the first six peaks of G(r) individually as functions of annealing temperature. (c) The intensity ratio R of the second line relative to the third line in Mössbauer spectra and coercivity H c as functions of annealing temperature.